Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.5 - Solving Equations Containing Rational Expressions - Exercise Set - Page 524: 32



Work Step by Step

$1+\dfrac{3}{x+1}=\dfrac{x}{x-1}$ Multiply the whole equation by $(x+1)(x-1)$ to eliminate all denominators: $(x+1)(x-1)\Big(1+\dfrac{3}{x+1}=\dfrac{x}{x-1}\Big)$ $(x+1)(x-1)+3(x-1)=x(x+1)$ Evaluate the indicated operations: $x^{2}-1+3x-3=x^{2}+x$ Take all terms to the left side and simplify the equation by combining like terms: $x^{2}-x^{2}+3x-x-1-3=0$ $2x-4=0$ Solve for $x$: $2x=4$ $x=\dfrac{4}{2}$ $x=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.